KESELAMATAN PENERBANGAN: TEORI DAN PROBLEMATIKA (AVIATION SAFETY: THEORY AND PROBLEMATIC) - Riadhy, Adhy (Indonesia Law Review, 2012)
“Keselamatan Penerbangan: Teori dan Problematika (Aviation Safety: Theory and Problematic)” is written by aviation practioner in Indonesia. The writer explores the aviation problematic based on his experience in more than three decades. Many issues out of box in aviation arise in this book, such as “Kebenaran Dalam Penerbangan (The Truth in Aviation)” which is focus on international aviation policy and regulations made by ICAO through research and development (scientific truth) and written on 18 Annexes and relevant documents, as living guidances of standards and recommended practices that must be implemented by states.